2019
DOI: 10.1088/2040-8986/ab0191
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap on superoscillations

Abstract: Superoscillations are band-limited functions with the counterintuitive property that they can vary arbitrarily faster than their fastest Fourier component, over arbitrarily long intervals. Modern studies originated in quantum theory, but there were anticipations in radar and optics. The mathematical understanding—still being explored—recognises that functions are extremely small where they superoscillate; this has implications for information theory. Applications to optical vortices, sub-wavelength microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 118 publications
2
116
0
1
Order By: Relevance
“…We prove the practicality of imaging using a number of metamaterial lenses with different fields of view and effective NAs, demonstrating resolution close to the size of superoscillatory hotspot and beating the conventional "diffraction limit." Imaging of more complex objects like living cells or silicon photonic chips with superoscillatory lenses is practical [32,33]. Importantly, ultrathin superoscillatory metamaterial superlenses, which are capable of continuous amplitude and phase modulation, can be manufactured by well-established high-throughput nanomanufacturing processes such as high-resolution lithography and can be easily scalable to operate at any wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…We prove the practicality of imaging using a number of metamaterial lenses with different fields of view and effective NAs, demonstrating resolution close to the size of superoscillatory hotspot and beating the conventional "diffraction limit." Imaging of more complex objects like living cells or silicon photonic chips with superoscillatory lenses is practical [32,33]. Importantly, ultrathin superoscillatory metamaterial superlenses, which are capable of continuous amplitude and phase modulation, can be manufactured by well-established high-throughput nanomanufacturing processes such as high-resolution lithography and can be easily scalable to operate at any wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…Since the recent proposal of the concept of superoscillation, [ 13,14 ] there has been growing interest in developing optical super‐resolution devices for far‐field operation without evanescent waves. [ 15,16 ] According to this concept, an arbitrary small point‐spread function (PSF) can be achieved by engineering the wave front of the incident wave through a properly designed amplitude‐phase mask. [ 17 ] This opens an alternative way toward far‐field optical super‐resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The classical restriction on the resolution of focusing, caused by the diffractive nature of light and known as Abbe's diffraction limit, has historically been a strong constraint on the resolution of various optical systems. In recent years, however, it has been shown that light can be focused well below the diffraction limit in the far field by exploiting the phenomenon of superoscillation, where light oscillates faster than its highest Fourier component in a specific local region [1][2][3][4] . Optical superoscillations have been realized by means of spatial light modulators, optical eigenmode methods, metasurfaces, and binary lenses [5][6][7][8][9][10] .…”
Section: Sub-wavelength Annular-slitassisted Superoscillatory Lens Fomentioning
confidence: 99%